2017
DOI: 10.14196/mjiri.31.56
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intramuscular progesterone with oral nifedipine for treating threatened preterm labor: A randomized controlled trial

Abstract: Background: Threatened preterm labor (TPL) is the leading cause of hospitalization during pregnancy. Tocolytic agents are the primary therapeutic options for TPL. The aim of this study is to compare intramuscular progesterone with oral nifedipine as a tocolytic agent. Methods: This randomized controlled trial was carried out in a teaching hospital (Shahid Akbarabadi) in Tehran, Iran, from December 2011 to November 2012. Three hundred and fifteen singleton pregnant women aged >18 yrs at 26-34 weeks’ gestation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…One study compared single dose antibiotic prophylaxis to a multi-day course for routine C-section and found there was no significant difference in stillbirth or neonatal mortality between the two [ 97 ]. Vaginal progesterone for tocolysis in twin pregnancies was not found to increase gestational age at delivery [ 98 ], and a comparison of IM progesterone and nifedipine for threatened preterm labour found no significant change in either time to delivery or rates of Neonatal Intensive Care Unit (NICU) admission [ 99 ].…”
Section: Resultsmentioning
confidence: 99%
“…One study compared single dose antibiotic prophylaxis to a multi-day course for routine C-section and found there was no significant difference in stillbirth or neonatal mortality between the two [ 97 ]. Vaginal progesterone for tocolysis in twin pregnancies was not found to increase gestational age at delivery [ 98 ], and a comparison of IM progesterone and nifedipine for threatened preterm labour found no significant change in either time to delivery or rates of Neonatal Intensive Care Unit (NICU) admission [ 99 ].…”
Section: Resultsmentioning
confidence: 99%
“…17 Nifedipine has better safety profile than beta agonists and MgSO4. 18 In present study, we compared the effectiveness of nifedipine against vaginal progesterone to prevent preterm labour. We found that vaginal progesterone is more effective than nifedipine for the prevention of preterm labour.…”
Section: Discussionmentioning
confidence: 99%
“…Drugs adverse effects were statistically significant among the 3 studied groups we had found that headache, palpitation and hot flushes more obvious in group I and II but less in group III (figure 3). Many previous studies had been discussed the efficacy of progesterone, calcium channel blockers or any of the other tocolytics in prevention of threatened preterm labor, from those studies, Ladan et al [24] studied the comparative efficiency between Nifedipine and intramuscular progesterone, the success rates with intramuscular progesterone and oral Nifedipine were 83% and 82.7%, respectively but there was no a statistically significant difference in the previously mentioned 2 agents concerning the gestational age at time of delivery, mode of delivery, neonatal birth weight, in the rate of NICU admission and hospitalization period, These results and findings were in harmony with that reported in our study as regards to neonatal outcome but in our study the prevalence of preterm labor was higher in Dydrogesterone than Nifedipine this may can be explained because of the route and type of progesterone was different from that used in Ladan et al…”
Section: Discussionmentioning
confidence: 99%